2004
DOI: 10.1021/ac0355045
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Characterization of Nucleic Acids Modified by Structural Probes Using High-Resolution Tandem Mass Spectrometry and Automated Data Interpretation

Abstract: A top-down approach based on sustained off-resonance irradiation collision-induced dissociation (SORI-CID) has been implemented on an electrospray ionization (ESI) Fourier transform mass spectrometer (FTMS) to characterize nucleic acid substrates modified by structural probes. Solvent accessibility reagents, such as dimethyl sulfate (DMS), 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide metho-p-toluenesulfonate (CMCT), and beta-ethoxy-alpha-ketobutyraldehyde (kethoxal, KT) are widely employed to reveal the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 57 publications
2
90
0
Order By: Relevance
“…All data were acquired in broadband mode and were processed using XMASS 7.0.8 (Bruker). Data reduction and analysis were performed with the aid of MS2Links [51] and the Mongo Oligo Mass Calculator version 2.05 made …”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…All data were acquired in broadband mode and were processed using XMASS 7.0.8 (Bruker). Data reduction and analysis were performed with the aid of MS2Links [51] and the Mongo Oligo Mass Calculator version 2.05 made …”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Tandem mass spectrometry has been extensively used to identify the sequence of oligonucleotide samples [42][43][44][45][46] and characterize their covalent modifications [47][48][49][50][51] based on characteristic ions series produced by fragmentation of the nucleic acid backbone. In contrast, gas-phase activation of small ligand-nucleic acid complexes has been more actively pursued to investigate their stability rather than to map the actual binding sites [52][53][54][55][56].…”
mentioning
confidence: 99%
“…Applied to PDG and BDG reaction mixtures, each protease provided series of hydrolytic peptides, which afforded excellent sequence coverage and allowed for the characterization of probe adducts. The identification of conjugated products was completed by using LINKS [68], a software package designed to support the analysis of crosslinked biomolecules. As summarized in Table 2, the results indicated that the crosslinkers were capable of modifying all available sites, although with different outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Probe-to-substrate ratios should always be kept as low as possible to reduce crosslinking yields and to minimize the risk of detecting sparsely populated conformational states [25,74]. Titration schemes in which the amount of probe is increased in stepwise fashion can effectively differentiate primary modification sites from secondary sites that are exposed only as a result of conformational changes induced by initial alkylation [68]. Yield and position of crosslinked products should be also evaluated by repeating probing reactions under a wide variety of environmental conditions that influence substrate conformation [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation